Case report: Bilateral eye injuries in members of one family due to a cluster munition in Ukraine - Nowomiejska, Katarzyna; Adamczyk, Katarzyna; Haszcz, Dariusz; Preys, Nataliya; Rejdak, Robert (Frontiers in Medicine, 2023)
The aim of the study was to report the effects of surgical treatment of three victims of a cluster munition in Ukraine. A 32-year-old woman and her sons—6-year-old male twins—presented in Poland after 18 days of delay in treatment. All ocular injuries were bilateral. One of the boys presented with total retinal detachment and a post-traumatic cataract as well as corneal sutures in one eye and a post-traumatic cataract in the other eye. The other boy had already developed atrophy in one eye and a vitreous hemorrhage in the other eye. The woman suffered from bilateral post-traumatic cataract with multiple glass intraocular foreign bodies (IOFBs). The surgical treatment included cataract surgery with intraocular lens implantation in three eyes, removal of IOFBs in one eye, and enucleation of the atrophic eye with implantation of an ocular prosthesis preventing constriction of face tissues. The eye with retinal detachment underwent pars plana vitrectomy, and the vitreous hemorrhage resolved itself. Postoperatively, visual acuity improved significantly in four of six eyes. Only in the eye with an open-globe injury and persistent retinal detachment, the final visual acuity was still poor. In conclusion, cluster munition may lead to bilateral ocular trauma with IOFBs, open-and close-globe injuries, and severe vision loss if left untreated. Modern ophthalmic surgery leads to vision with IOL improvement and solving the eyes after severe combat injury.